OHCA survey in Lombardy: comparison between years 2014 and 2019 (pre COVID-19) - Andreoletti, Mirko; Bonora, Rodolfo; Botteri, Marco; Villa, Cinzia Licia; Sechi, Giuseppe Maria; Zoli, Alberto; Villa, Guido Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The incidence of Out of Hospital Cardiac Arrest (OHCA) is estimated at 1/1000 persons/year. In the pre-Covid-19 era world, OHCA survival rate in Europe was 7-6%. The main objective is to analyze OHCA survival in the Lombardy region by highlighting the factors related to both the victims’ characteristics and the chain of survival. Methods: All OHCAs were grouped into four pre-established periods in 2019 (14-23 January; 15-24 April; 15-24 July; 14-23 October). Following the Utstein method, we selected witnessed OHCAs with presumed cardiac etiology. The outcome of each case was collected in four moments in time: Return of spontaneous circulation (ROSC), Emergency Department (ED), 24 hours and 30 days. The neurological outcome 30 days after OHCA was also investigated and stratified with the Cerebral Performance Category Score (CPC). Results: We selected 456 cases of OHCA with witnessed cardiac etiology. ROSC was achieved in 121 cases (26.5%), survival in the Emergency Departments in 110 patients (24.1%), after 24 hours in 86 (18.86%) and after 30 days in 72 (15.8%). Male sex was shown to improve OHCA survival. A shockable presentation rhythm, Cardiopulmonary Resuscitation (CPR) performed by bystanders and the activation of Public Access Defibrillation (PAD) positively influenced OHCA outcome. Conclusions: Males are more predisposed to incur an OHCA event than females, but they have greater chances of survival. Factors most related to survival are: shockable rhythm, bystanders CPR and the activation of a PAD. (www.actabiomedica.it)